The texts of everyday life: public and private identities in vernacular literacy practices - Hamilton, Mary; Barton, David (Cadernos de Linguagem e Sociedade, 2010)
This paper draws on data collected during an ethnographic study of literacy practices in one local community. It focuses on a case study of one woman, who was editor of a Residents Assocation newsletter and the editorials she wrote. We look at the “text world” of these editorials and examine the ways in which the editor positions herself in relation to the other inhabitants ”“ groups and individuals ”“ who populate this world. Three kinds of data were collected and juxtaposed in our research: observations of literacy practices, in-depth interviews with participants and the documents entailed in the literacy practices. This research, which starts from a study of literacy practices, leads us to discover new categories of vernacular texts ”“ in this case community group newsletters ”“ which provide a rich and unusual source of data for exploring many issues to do with writer identity, genre, authorship and collaborative writing practices in everyday life. We argue that bringing together the study of practices and the study of texts offers an enhanced methodology for researching discourse in society.